THE INCIDENCE OF DERMATITIS IN FISHERMEN IN BONTANG CITY, EAST KALIMANTAN, INDONESIA - Setyowati, Dina Lusiana; Risva, Risva; Anwar, Andi; Afiah, Nurul (Public Health of Indonesia, 2019)
Background: Occupational skin diseases are the most common occupational diseases in many countries. Dermatitis has become one of the top 10 occupational diseases (PAK) based on the potential incidence, severity, and prevention ability. Fishermen are one of the oldest occupations and have a high risk of occupational accidents or occupational diseases, which one of the risks is dermatitis due to the exposure to sea water containing salt which is high enough to absorb the water from the skin.Objective: This study aims to determine the incidence of dermatitis, working duration, duration of exposure, history of skin diseases, use of personal protective equipment, and personal hygiene in the fishing communities in North Bontang.Methods: This study is an analytic observational study with a cross sectional study design. The population in this study was the fishing community in Loktuan Urban-Village, North Bontang. The samples were taken with the purposive sampling and a sample of 154 fishermen was obtained. The data were collected with a questionnaire that has been tested for the validity. The statistical analysis was conducted by Chi Square test with a significance level of 0.05.Results: The results showed that the history of skin diseases, the duration of exposure are related to the incidence of dermatitis in fishermen.Conclusion: Further research is needed to find out other risk factors that can cause dermatitis in fishermen.